Intentional self-harm and suicide epidemiological profile in North India. (1st March 2011) - Aggarwal, A D; Garg, M; Gorea, R K; Singh, H; Singh, A
Abstract : Self-directed violence is deliberate self-injury, self-abuse or suicidal behaviour including attempted or completed suicides. Fabricated, fictitious, forged or invented wounds may be self-inflicted or self-suffered. Such injury is a major problem of forensic experts. Minimal of literature is available pertaining to the study of the fabricated injuries and specifically, no authentic criterion is laid down to label, which injury should be declared as fabricated. Self-directed violence has a large number of underlying causes. Apart from demographic factors like age and sex; psychiatric, biological, social and environmental factors are important apart from the factors related to individuals life history. The overall suicide rate was 28.9 per 100 000 population; the highest burden was among men (89%). The age group 21–30 years was most prone to suicide, accounting for 46% suicidal deaths. Most people died through self-poisoning (64%), hanging (25%) or self-immolation (10%). A significant group of injuries hitherto unaccounted, were fabricated injuries where the intentional was some ultimate gain or harm to others. The cultural epidemiology of deliberate self-harm, it is argued, is critical to planning for suicide and injury prevention and promotion of safety. The present study was designed to investigate the different methods of self-destruction, age and gender susceptibility to suicide, the groups particularly affected and the underlying motivating factors for such an extreme step among north Indian people. Various suggestions relating to decreasing the tensions of modern life, proper use and storage of agrochemicals and financial improvement of farmers have been put forward.